2017
DOI: 10.1016/j.jaip.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Food Allergy Phenotype and Health Care Utilization among US Children

Abstract: FA phenotypes and health care utilization differ among children of different racial and/or ethnic backgrounds in the United States that put AA and Hispanic children at higher risks of adverse outcome than white children. These differences include coexistent atopic conditions, less well recognized food allergens, and higher rates of anaphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 24 publications
2
52
0
1
Order By: Relevance
“…In general, anaphylaxis was common [79, 20, 21], more associated with repeated use of epinephrine [27] and more fatal [23] among Caucasians compared to Black, Latino/Hispanic and Asian ethnicities. In contrast, Mahdavinia et al (2017) reported that Caucasians had a lower rate of food allergy associated anaphylaxis than African American and Hispanic children [37]. Additionally, Buka et al (2015) reported that Caucasians had less incidence, and were less likely to present with severe anaphylactic symptoms than South Asian British children living in Birmingham [38].…”
Section: Discussionmentioning
confidence: 99%
“…In general, anaphylaxis was common [79, 20, 21], more associated with repeated use of epinephrine [27] and more fatal [23] among Caucasians compared to Black, Latino/Hispanic and Asian ethnicities. In contrast, Mahdavinia et al (2017) reported that Caucasians had a lower rate of food allergy associated anaphylaxis than African American and Hispanic children [37]. Additionally, Buka et al (2015) reported that Caucasians had less incidence, and were less likely to present with severe anaphylactic symptoms than South Asian British children living in Birmingham [38].…”
Section: Discussionmentioning
confidence: 99%
“…158, 159 Reasons for these ethnic disparities remain unclear, but may reflect true genetic differences, environmental factors, including socioeconomic status, or a combination of factors. Nevertheless, a handful of genetic polymorphisms have been described that may influence development of anaphylaxis.…”
Section: Genetic Diversity/host Factors Influencing Anaphylaxismentioning
confidence: 99%
“…in a retrospective cohort study of children aged 0‐17 years consulting at two allergy tertiary care centres in the USA. The African American or Hispanic children were found to have more severe FA profiles more commonly associated with allergic comorbidities than the non‐Hispanic White children . Corn, seafood and fish allergies were more frequent in African American and Hispanic children, wheat or soybean allergies more common in those of African American origin, and nut allergies in White children.…”
Section: Determinants Of Severe Food Allergy Phenotypesmentioning
confidence: 93%
“…The African American or Hispanic children were found to have more severe FA profiles more commonly associated with allergic comorbidities than the non-Hispanic White children. 31 Corn, seafood and fish allergies were more frequent in African American and Hispanic children, wheat or soybean allergies more common in those of African American origin, and nut allergies in White children. These differences may be attributed to cultural dietary habits, food introduction practices, different living conditions and genetic backgrounds.…”
Section: Influence Of Gender and Ethnic Backgroundmentioning
confidence: 95%